Effect of retained austenite on short fatigue cracks in austempered ductile cast iron (ADI) - Marrow, T; Cetinel, H; Wang, C; Bayati, H (2000)
The fatigue resistance in ductile irons generally increases with tensile strength and matrix hardness as the matrix microstructure varies from ferrite through ferrite/pearlite and ausferrite to quenched and tempered martensite. However, there is a maximum in the fatigue limit in austempered ductile iron (ADI) microstructures at intermediate strength. This is also associated with high ductility, and is due to retained austenite in the ausferrite matrix. This paper investigates the role of microstructure in the control of short fatigue crack propagation in ADI. The length of arrested cracks, which nucleated at graphite nodules, is controlled by the ausferrite lath length distribution. Cracks are therefore arrested by the ausferrite packet and prior austenite grain boundaries. This indicates that refinement of the microstructure, for example by the use of lower austenitisation temperatures, could decrease the size of subcritical crack nuclei, which would increase the fatigue endurance limit.